THE ROLE OF ACADEMIC SUPERVISORS IN EDUCATIONAL PSYCHOLOGICAL MANAGEMENT OF UIN SULTAN MAULANA HASANUDDIN BANTEN STUDENTS - Suryapermana, Nana; Rosidah, Rosidah; Subekhan, Moch. (International Journal of Economy, Education and Entrepreneurship (IJE3), 2025)
This study aims to analyze the role of Academic Supervisors in the management of student educational psychology at UIN Sultan Maulana Hasanuddin Banten. The method used is qualitative with data collection techniques through interviews, observations, and documentation. The results of the study indicate that Academic Supervisors have an important role in providing academic guidance and supporting students' psychological development. Academic Supervisors function to help students plan their educational paths, choose appropriate courses, and provide solutions to academic problems. Academic Supervisors play a role in helping students overcome psychological challenges related to campus life, such as stress and academic anxiety. However, there are challenges faced by Academic Supervisors related to the excessive number of students, reducing the time to give full attention. This study concludes that strengthening psychology training for Academic Supervisors, as well as increasing the number of Academic Supervisors, can increase the effectiveness of the guidance provided. This will support students' academic and psychological development, create a more conducive academic environment and support student success in college.